Catalytic Reduction in Organic Synthesis. Band 1 und 2, Science of Synthesis, Workbench Edition Herausgegeben von J. G. de Vries. (8th November 2019) - Vidal‐Ferran, Anton
Abstract : Thieme, 2018. 992 S., Broschur, 449.00 €.—ISBN 9783132421486